2020
DOI: 10.1109/access.2019.2962757
|View full text |Cite
|
Sign up to set email alerts
|

Improving Time Series Reconstruction by Fixing Invalid Values and its Fidelity Evaluation

Abstract: MODIS time series data have been widely used in the research of regional and global ecosystems and climate change. For vegetation monitoring, vegetation indices such as NDVI (normalized difference vegetation index), EVI (enhanced vegetation index) and NBR (normalized burn ratio), are usually derived from MODIS reflectance data. However, noise usually makes it difficult to generate reliable time series of vegetation indices. Although some methods have been developed for reconstructing NDVI time series data, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…33,34 The HANTS method was superior to the SG filter in dealing with noise, which is in line with several other studies that found similar results for NDVI reconstruction. 35 However, the HANTS method shows some instability at some points in the two profiles depicted in Figure 5. This is the case in points where the HANTS showed large deviations from the raw data, in which the denoised data were larger than the original data.…”
Section: Resultsmentioning
confidence: 96%
“…33,34 The HANTS method was superior to the SG filter in dealing with noise, which is in line with several other studies that found similar results for NDVI reconstruction. 35 However, the HANTS method shows some instability at some points in the two profiles depicted in Figure 5. This is the case in points where the HANTS showed large deviations from the raw data, in which the denoised data were larger than the original data.…”
Section: Resultsmentioning
confidence: 96%
“…These five variables had different temporal resolutions, and they were processed into an 8-day composite to facilitate the analyses of drought. Because the 16-day vegetation products had many missing pixels due to the clouds in summer [71][72][73], we used monthly EVI products provided through a gap-filling process. Since the vegetation vitality changed gradually over time like a cosine curve, the monthly EVI was interpolated at an 8-day interval by applying a cubic spline method [71].…”
Section: Methodsmentioning
confidence: 99%
“…The reflectivity of the cloud pollution area (area affected by clouds and cloud shadows) was abnormal, and the NDVI was lower than that in the unpolluted area [ 25 , 26 ]. To effectively remove the abnormal effect on reflectivity, it was essential to remove the cloud (include cirrus) [ 27 ] pollution pixels from the remote-sensing satellite images.…”
Section: Study Area and Dataset Preprocessingmentioning
confidence: 99%